2019
DOI: 10.17233/sosyoekonomi.2019.02.14
|View full text |Cite
|
Sign up to set email alerts
|

BREXIT and the J-Curve Hypothesis for the UK: A Nonlinear ARDL Approach

Abstract: In this study, we investigate the validity of the J-curve hypothesis based on the bilateral trade models between the UK and its 17 main trading partner countries over the period of 1981Q1-2015Q1, by applying Nonlinear Autoregressive Distributed Lag (NARDL) cointegration approach. The results of this study suggest no evidence supporting the J-curve hypothesis between the UK and any of its 17 trading partners. We also find that depreciations and appreciations in value of the GBP have asymmetric effects on the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
2
0
5
Order By: Relevance
“…The J‐curve hypothesis suggests that short and sudden declines of previously stable and flourishing economic growth rates lead to social and economic revolutions/unrest. The J‐curve was investigated empirically by Sivrikaya and Ongan (2019) and found to have strong compatibility with Brexit data, which implies that the Dogville effect may as well exist as a phenomenon behind the Brexit vote too.…”
Section: The Cbd Mechanism Behind the Left‐behind Votementioning
confidence: 99%
“…The J‐curve hypothesis suggests that short and sudden declines of previously stable and flourishing economic growth rates lead to social and economic revolutions/unrest. The J‐curve was investigated empirically by Sivrikaya and Ongan (2019) and found to have strong compatibility with Brexit data, which implies that the Dogville effect may as well exist as a phenomenon behind the Brexit vote too.…”
Section: The Cbd Mechanism Behind the Left‐behind Votementioning
confidence: 99%
“…While non-linear ARDL models are generally more statistically robust and tend to identify J-curve effect in a greater number of cases compared to the linear models, a number of studies nonetheless demonstrated the absence (or rather limited presence) of the J-curve even when non-linear ARDL is used. These studies included Akoto and Sakyi (2019), who did not identify the J-curve in the non-linear model in the case of aggregate trade of Ghana; Sivrikaya and Ongan (2019), who examined, using non-linear ARDL, the UK bilateral trade with seventeen trading partners but did not detect J-curve in any of the cases; and Bahmani-Oskooee et al (2016) who applied non-linear ARDL to the bilateral trade of the UK with six major trading partners, but identified significant effect only in the case of the UK–US trade (despite the presence of asymmetries across the cases, and meaningful diagnostic statistics). In the papers that generally give support to the J-curve phenomenon based on non-linear ARDL, the effect was not always observed in every or the majority of cases, for example, in 5 out of 21 among China’s trading partners (Bahmani-Oskooee et al, 2018), or in three out of eight among Pakistan’s partners (Iqbal et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…2018;Ongan vd. 2018;Sivrikaya & Ongan, 2019;Ölmez, 2021). Junz & Rhomberg (1973) çalışmalarında, ülkeler arasında gerçekleşen dış ticarette ürün miktarının fiyata olan tepkisinde beş farklı gecikmenin olabileceğini belirtmişlerdir.…”
Section: Introductionunclassified